Relationship between maternal periodontal disease and low birth weight babies - Ahmad Haerian-Ardakani; Zia Eslami; Fahimeh Rashidi-Meibodi; Alireza Haerian; Pantea Dallalnejad (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Periodontal infections, which serve as a reservoir of inflammatory mediators, may pose a threat to the fetal-placental unit and cause adverse pregnancy outcomes. Objective: The aim of this study was assessing the periodontal status of women during puerperium and determining the possible relationship between their periodontal disease and low birth weight delivery. Materials and Methods: This was a case-control study. The sample included 88 ex-pregnant women were seen at maternity hospitals of Yazd, Iran. Half of the mothers had low birth babies (LBW) (birth weight below 2500g- case group) and the others had normal weight babies (>2500g- control group). The mothers' data were obtained from medical files, interview and periodontal clinical examination carried out up to 3 days after delivery. Bleeding on probing, presence of supra-gingival calculus and CPITN (Community Periodontal Index for Treatment Needs) were used for periodontal assessment Results: Among the known risk factors of LBW babies, history of previous LBW infant among case mothers reached statistical significance (p=0.0081, Student t-test). Mothers of LBW infants had less healthy areas of gingiva (p=0.042), and more deep pockets (p=0.0006, Mann-Whitney test). Conclusion: The maternal periodontal disease can be a potential independent risk factor for LBW.